Rule of seagrass ecosystem as marine debris trap: A study case in seagrass ecosystems across a small island at Tanjungpinang city - Aditya Hikmat Nugraha; Rizki Rizki; Fadhliyah Idris (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Seagrass ecosystems have an essential function as a feeding, spawning and nursery areas for various marine biota, etc. There are threats to the sustainability of seagrass ecosystems' biodiversity, one of which is the dumping of garbage into the sea, which causes damage to coastal ecosystems. This study aimed to determine the species and cover of seagrass ecosystems and the type and density of marine debris in seagrass ecosystems in the waters of small islands of Tanjungpinang City. There are three stations: Dompak Island, Penyengat Island, and Los Island. This research was conducted in May-June 2023. Seagrass cover data was collected using the line transect method with a quadrat transect of 50 cm x 50 cm to observe the species and cover. Data collection on marine debris in the seagrass ecosystem was taken on transects with an area of 100 m x 100 m. Marine debris obtained is then grouped by type to calculate density and weight. The types of seagrasses found include Enhalus acoroides, Thalassia hemprichii, Cymodocea serrulata, Cymodocea rotundata, Halodule uninervis, Halodule pinifolia, Halophila ovalis, and Syringodium isoetifolium. The highest total seagrass cover is found on Los Island, with a value of 25.81% classified as poor with a sparse cover category. The types of marine debris found are plastic, glass, rubber, wood, and its derivatives. According to the number of pieces, the highest density of marine debris is plastic waste, resulting in 0.0079 items/m2, and the weight density is 0.0528 grams/m2 found at Los Island.Keywords:biodiversitydebrisplasticseagrasssmall island